Isolation by environment and recurrent gene flow shaped the evolutionary history of a continentally distributed Neotropical treefrog - Camurugi, Felipe; Gehara, Marcelo; Fonseca, Emanuel M.; Zamudio, Kelly R.; Haddad, Célio F.B. [UNESP]; Colli, Guarino R.; Thomé, Maria Tereza C. [UNESP]; Prado, Cynthia P.A. [UNESP]; Napoli, Marcelo F.; Garda, Adrian A. (Wiley, 2021)
Aim: Phylogeographic studies show how historical and current changes in landscapes shape the geographic distribution of genetic diversity in species of animals and plants. In particular, for the species of the Diagonal of Open Formations (DOF), the compartmentalization of the Central Brazilian Plateau (CBP) during the Tertiary and climatic oscillations during the Quaternary have often been invoked to explain the origin and current patterns of biodiversity. We investigated how landscape changes and climatic oscillations shaped the distribution and diversification history of a widespread South American treefrog. Location: South American Diagonal of Open Formations (DOF) including Caatinga, Cerrado, and Chaco biomes. Taxon: Treefrog Boana raniceps. Methods: We used a multi-locus dataset from 288 individual frogs collected at 115 localities throughout most of the species’ distribution. We used population assignment analysis, species distribution models, historical demography models, approximate Bayesian computation and landscape genetic analyses to test alternative hypotheses of diversification. Results: We found two genetic lineages that diverged during the mid-Pleistocene with continued gene flow. Approximate Bayesian computation supported a scenario of isolation with migration until the Last Glacial Maximum, followed by more recent population expansion in north-eastern Brazil and stability at the southwest in South America. Isolation by environment was the best predictor of genetic distance between populations, which is in accordance with their different environmental niches. As Boana raniceps is a lowland species, steep slopes in the CBP likely restrained gene flow enough to sustain population divergence. We found evidence for major range contraction during the Last Glacial Maximum, raising the possibility of synergic action of climate change and the CBP compartmentalization in regulating migration. Main conclusions: Our findings highlight how landscape and climatic changes can shape the diversification of DOF biota. Past climatic fluctuations and environmental resistance due to topography acted in concert, forming a semipermeable barrier to gene flow, promoting intraspecific differentiation in a continentally distributed species.
Keywords: Anura; approximate Bayesian computation; Boana raniceps; isolation by environment; landscape genetics; lowland species; Quaternary climatic fluctuation; riverine effects; South America; topography